Engaging With Health Consumers in Scientific Conferences-As Partners not Bystanders - Bronwyn Newman; Janelle Bowden; Rebecca Jessup; Lauren J. Christie; Ann Livingstone; Mitchell Sarkies; Anagha Killedar; Carole Vleeskens; Mashreka Sarwar; Thit Tieu; Saran Chamberlain; Reema Harrison; et al. (Wiley, 2024)
ABSTRACT Introduction It is now widely recognised that engaging consumers in research activities can enhance the quality, equity and relevance of the research. Much of the commentary about consumer engagement in research focuses on research processes and implementation, rather than dissemination in conference settings. This article offers reflections and learnings from consumers, researchers and conference organisers on the 12th Health Services Research Conference, a biennial conference hosted by the Health Services Research Association of Australia and New Zealand (HSRAANZ). Method We were awarded funds via a competitive application process by Bellberry Limited, a national not‐for‐profit agency with a focus on improving research quality, to incorporate consumer engagement strategies in conference processes and evaluate their impact. Findings Strategies included consumer scholarships, a buddy system, designated quiet space and consumer session co‐chairs; the reflections explored in this paper were collected in the funded, independent evaluation. Our insights suggest a need for more structured consumer involvement in conference planning and design, as well as the development of specific engagement strategies. Conclusion To move toward active partnership in scientific conference settings, our experience reinforces the need to engage consumers as members in designing and conducting research and in presenting research and planning conference content and processes. Public Contribution Consumer engagement in research dissemination at conferences is the focus of this viewpoint article. Consumers were involved in the conception of this article and have contributed to authorship at all stages of revisions and edits.